Assessing the Influence of Tourism Competitiveness on the Development of Tourism Destinations: A Case Study of Queen Elizabeth Nation Park. - Turyamureeba, Frankline (Kabale University, 2024)
This study delved into the relationship between tourism competitiveness and the evolution of tourism destinations. By scrutinizing the factors that enhance a destination's appeal to tourists, such as its diverse ecosystems, abundant biodiversity, and well-established infrastructure, the research aims to unravel the dynamics that drive overall progress. The investigation goes beyond the surface to assess how a destination's competitive edge translates into tangible economic benefits. Specifically, the focus is on examining the potential outcomes, including the growth of businesses in the tourism sector and the enhancement of overall infrastructure. Through a meticulous analysis of these facets, the research aims to provide destination managers with valuable insights into leveraging tourism as a catalyst for sustainable development. The findings are poised to guide strategic decision-making, enabling destination managers to harness the full potential of tourism while ensuring its alignment with principles of sustainability and long-term viability. As tourism continues to play a pivotal role in global economies, understanding and optimizing its competitive dynamics become imperative for fostering responsible and balanced growth in tourism destinations